An Adaptive Image-stitching Algorithm for an Underwater Monitoring System. (14th October 2014) - Hengyu, Li; Jun, Luo; Huang, Chaojiong; Yang, Yi; Xie, Shaorong
Against the narrow range of sonar images for underwater monitoring, an adaptive sonar image-stitching algorithm is proposed in this paper. Compared with conventional sonar image-stitching algorithms, this algorithm can be applied to stitch sonar images with fewer features and better results. This paper first introduces the hardware platform of the underwater monitoring system and a 3D model of the underwater rotational mechanism. Next, related image pre-processing is conducted to improve its accuracy. A SURF algorithm is then applied to extract the speeded-up robust feature (SURF) points. Compared with a threshold, if the number of SURF points is larger, the SURF algorithm is applied to stitch the sonar images or else the phase correlation method is selected to mosaic the sonar images. Finally, a weighted smoothing fusion algorithm based on a maintained boundary is proposed to fuse the sonar images. The algorithm is verified to give good performance in mosaicing sonar images by an experimental study.